Effects of Green Technology Support Policies on Carbon Dioxide Emissions - Richhild Moessner (Center for Economic Studies and ifo Institute (CESifo), 2024)
This paper provides ex-post empirical evidence on the effects of green technology support policies, in comparison with other climate policies, on carbon dioxide emissions at the aggregate national level. The paper uses cross-country dynamic panel estimation for a sample of 38 countries over the period from 1990 to 2015, controlling for macroeconomic determinants such as economic development, GDP growth, urbanisation and the energy mix. It uses a new index which measures the strength of green technology support policies, including separate sub-indices for the public support of expenditure on research and development of low-carbon energy technologies, and for the support of the adoption of wind energy and of solar energy. We find that an increase by one index point of the green technology support policy index leads to a significant reduction of around 0.9% in CO2 emissions per capita in the short run, and of around 3.7% in the long run. An increase by one index point of the green R&D expenditure support policy index leads to a significant reduction of around 0.4% in CO2 emissions per capita in the short run, and of around 1.7% in the long run. An increase by one index point of the wind energy support policy index leads to a significant reduction of around 0.5% in CO2 emissions per capita in the short run, and of around 2.1% in the long run.
Keywords: Q00; Q48; Q58; Q55; Q40; Q50; 330; green technology support policies; solar energy; wind energy; climate policigreen technology support policies; solar energy; wind energy; climate policies; carbon tax; carbon dioxide; climate changees; carbon tax; carbon dioxide; climate change; emissions